Analysis of Decision No. 245/Pid.Sus/2023/Pn.Jkt.Sel Reviewed Based on The Value of Justice, Purposiveness and Legal Certainty - Hermansyah, Regita Elvitri; Nuladhani, Almirah Fitri; Sie, Angel Melinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Nowadays, violence against household assistants (ART) often occurs, especially due to unequal power relationships. Quoting data obtained from Simfoni-PPA, starting from January 2023 there were 28,930 cases of violence, of which 25,335 cases were women and 18,749 of them occurred within the household. This then attracted the author toxconduct a more in-depthxstudyxof cases of violence against household members in Decision No. 245/Pid.Sus/2023/PN.Jkt.Sel is reviewed based on the valuesxofxjustice, expediency and legal certainty. This research uses a type of normative juridical legal research, namely researchxcarried outxby examining library materialsx(Library Research) or obtaining data in research obtained through secondary data. The research results show that in Decision No. 245/Pid.Sus/2023/PN.Jkt.Sel, legal certainty is reflected in the imposition ofxpunishment in thexform of criminal sanctions on the defendant, legal benefits are given to victims by imposing punishment on the defendants and on the defendants themselves as a reflection on their actions. Meanwhile, the value of justice that is fulfilled is only procedural justice without considering substantive justice, where the judge does not take much into account the trauma experienced by the victim after the act of violence occurred.